Immune checkpoint Ab enhances the antigen-specific anti-tumor effects by modulating both dendritic cells and regulatory T lymphocytes. (1st March 2019) - Sun, Nai-Yun; Chen, Yu-Li; Lin, Han-Wei; Chiang, Ying-Cheng; Chang, Chi-Fang; Tai, Yi-Jou; Chen, Chi-An; Sun, Wei-Zen; Chien, Chung-Liang; Cheng, Wen-Fang
Abstract: We determined the anti-tumor effects and possible mechanisms of an antigen-specific DNA vaccine combined with PD-1 or CTLA-4 blockade. Using the HPV16 E6/E7 + syngeneic mouse tumor model, we investigated whether anti-CTLA-4 antibody (Ab) or anti-PD-1 Ab increases the antigen-specific anti-tumor effects and immune response induced by CTGF/E7 chimeric DNA vaccine and the possible mechanisms. Anti-PD-1 Ab or anti-CTLA-4 Ab combined with E7-specific DNA vaccine generated more potent antigen-specific immunity, including anti-E7 Abs and the number and cytotoxic activity of E7-specific cytotoxic CD8 + T lymphocytes, and anti-tumor effects than E7-specific DNA vaccine alone. In addition, the number of systemic and intratumoral Tregs was lower with the anti-PD-1 or anti-CTLA-4 Ab and E7-specific DNA vaccine. Furthermore, anti-PD-1 and anti-CTLA-4 Abs could enhance the maturation and abilities of intratumoral DCs to activate E7-specific cytotoxic CD8 + T cells. Immune checkpoint blockade overcomes the immunosuppressive status of the tumor-microenvironment to enhance the antigen-specific immunity and anti-tumor effects generated by an antigen-specific DNA vaccine. Antigen-specific immunotherapy combined with immune checkpoint blockade can be a novel strategy in clinical cancer therapy. Highlights: Immune checkpoint blockade could enhance the antigen-specific anti-tumor effects. Immune checkpoint blockade could reduce intratumoral Treg cells and enhance the maturation and abilities of intratumoral DCs. Immune checkpoint blockade could overcome the immunosuppressive status of the tumor micro-environment.